Behavior and cognitive functioning in Witteveen–Kolk syndrome - van Dongen, Linde C. M. (Am J Med Genet A, 2020)
Witteveen–Kolk syndrome (WITKOS) is a rare neurodevelopmental disorder characterized by developmental delay/intellectual disability, facial dysmorphisms, and short stature. The syndrome is caused by loss of function of switch‐insensitive 3 transcription regulator family member A (SIN3A). Regarding behavioral functioning, Autism Spectrum Disorders (ASD), obsessive–compulsive behaviors, as well as Attention‐Deficit/Hyperactivity Disorder symptoms (ADHD) have been suggested. The present study explores various aspects of neurocognitive functioning in five individuals (age range 10–23) with WITKOS. Medical records and results of extensive neuropsychological assessment are used to describe developmental trajectories and neurocognitive profiles. Systematic analysis of medical records displays developmental difficulties described as ASD or ADHD in childhood, sleep problems and internalizing problems during adolescence. Results of cognitive assessments indicate profoundly disabled (n = 1), mildly disabled (n = 2), borderline (n = 1), and average (n = 1) levels of intelligence. Furthermore, results indicate weaknesses in speed of information processing/sustained attention in all participants, and difficulties in planning and maintaining overview in three participants. Furthermore, parent reports of behavioral functioning primarily suggest problems in social functioning. Implications of both cognitive problems and social–emotional vulnerabilities for counseling are discussed and supplemented with suggestions for interventions.